Romanticism reconsidered: Fanon, reciprocity and revolution (on Fanon’s ninetieth birthday) - Nigel C. Gibson (Acta Academica, 2015)
A romantic figure of “Third World” revolution and Black liberation, Frantz Fanon is often considered an advocate of violence as liberation therapy. Questioning the idea of Fanon as a romantic with an a priori set of ideas that he simply applied to new situations, I discuss the importance of contextualising Fanon’s work historically and dialectically. In addition, I am interested in how Fanon’s psychiatry papers, written while he was practising as a doctor in North Africa, provide another terrain to help elucidate Fanon’s active involvement as a situational critique.